Positivistic models of long-run labor allocation dynamics - Denis Stijepic (Journal of Economic Structures, 2017)
The three-sector framework (relating to agriculture, manufacturing, and services) is one of the major concepts for studying the long-run dynamics of the economic structure. We summarize the empirical/theoretical literature consensus by formulating 'economic laws' of long-run structural change in the three-sector framework. Based on these laws, we derive the (qualitative/geometrical) properties of the dynamic system describing the structural change and apply the standard concepts/theorems of dynamic systems analysis (e.g., omega limit sets) to derive the implications of these laws for the future (transitional and limit) structural dynamics in developed and developing countries. The advantage of this system theoretical approach is that it minimizes the dependence of the predictions on theoretical/ideological arguments, which are often criticized in economics.
Keywords: C61; C65; O41; O14; 330; Structural change; Labor; Re-allocation; Sectors; Agriculture; Manufacturing; Services; Long run; Dynamics; Trajectory; Geometry; Simplex; Dynamic systems